Pengembangan LKPD Berbasis Problem Based Learning Pembelajaran IPAS Kelas IV di SDN 03 Pontianak Selatan - Hidayat, Taufik; Halidjah, Siti; Ghasya, Dyoty Auliya Vilda (AS-SABIQUN, 2023)
This research generally aims to develop and produce problem-based learning worksheet products in the natural science subject on energy in the daily life of class IV SDN 03 Pontianak Selatan. This study uses the Research and Development (RnD) research and development method with the Borg and Gall method approach, which contains seven research steps namely potentials and problems, data collection, product design, product design validation, design revision, product testing, final product revision . At the product trial stage it was carried out in class IV SDN 03 Pontianak Selatan with a total of 32 students. The results of this study are in the form of problem-based learning worksheets for students on natural science subjects on energy in everyday life. The results of the material validity test showed a percentage of 81.54% with the interpretation of "Very Feasible" and the results of the design validity test showed a percentage of 83% with the interpretation of "Very Feasible". Student responses were divided into small and large groups, for the small group it showed a percentage of 85% with a "Very Good" interpretation then for the large group it showed a percentage of 86.10% with a "Very Good" interpretation. Based on the results of the overall assessment it can be concluded that the LKPD The developed problem-based learning is suitable for use in the science learning process on energy in everyday life in class IV SDN 03 Pontianak Selatan.